2011
DOI: 10.1007/s00784-011-0574-3
|View full text |Cite
|
Sign up to set email alerts
|

Histological and immunohistochemical evaluation of the peri-implant soft tissues around machined and acid-etched titanium healing abutments: a prospective randomised study

Abstract: A close spatial correlation has been described between the roughness of intraoral materials and the rate of bacterial colonisation. The aim of the present study in man was to conduct a comparative immunohistochemical evaluation of the inflammatory infiltrate, microvessel density, the nitric oxide synthases 1 and 3 and the vascular endothelial growth factor expression, the proliferative activity, and the B and T lymphocyte and histiocyte positivity in the peri-implant soft tissues around machined and acid-etche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 40 publications
3
54
0
Order By: Relevance
“…A rough surface can positively influence the attachment of cells [15,16,17]. The cell binding on the surface is mediated by the formation of hemidesmosomes, as in tooth [12,13,15,16,17,18]. The surface treatment could, therefore, influence the quality/quantity of these attachments as well as the healing process and host response [1,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rough surface can positively influence the attachment of cells [15,16,17]. The cell binding on the surface is mediated by the formation of hemidesmosomes, as in tooth [12,13,15,16,17,18]. The surface treatment could, therefore, influence the quality/quantity of these attachments as well as the healing process and host response [1,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, several techniques have been used to modify and treat the implant surface and studies about different treatments of the transgingival portion have been conducted [18,19,20,21]. From these studies, it seems that surfaces with homogeneous roughness can favor the epithelial and connective attachment and, therefore, the formation of a soft tissue barrier [1,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is still no consensus regarding treatment capable of producing the ideal implant surface, capable of accelerating the process of new bone formation 11 in the literature, in vitro research indicates that moderately rough surfaces with around 1.5µm Sa and 50% Sdr result in better performance and bone healing 7 . The surface topography of the implants influences the wettability of these and other parameters related to the osteogenesis process such as viability, growth curve, cellular adhesion and expression of proteins from the bone matrix 3,12,13 . In vivo studies have also confirmed the advantages of rough surfaces, such as greater bone-implant contact, acceleration of neo-osteogenesis and greater torque for their removal, when compared to machined implants 9,[14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…The blasting and the acid etching represent the treatments of implant surfaces used most when the objective is the creation of surface micro-roughness 11,13,18 . In vitro and in vivo 6 studies compared different types of surface treatments such as blasting, acid etching and acid etching after blasting.…”
mentioning
confidence: 99%
“…6 In addition, acid-etched implants could stimulate vascular formation, which would support and promote bone ingrowth. [7][8][9][10] Cortical implants with a pore size of 50-400 mm promote cortical bone ingrowth with relatively high fixation strength. 11 Another strategy for promoting bone growth into implants involves integrating cytokine growth factors, such as bone morphogenetic proteins (BMPs) into the implant.…”
mentioning
confidence: 99%